PEMAKAIAN BAHAN BAKAR GAS MENJADI ALTERNATIF BAGI KENDARAAN BERMOTOR BERBAHAN BAKAR PREMIUM - Indartono, Indartono (Gema Teknologi, 2012)
Indartono, in paper use of alternative fuel gas for a motor vehicle fuel oil explain that in many ways energy efficiency can also be more than just preservation. Energy efficiency is an attempt to reduce the use of petroleum materials and the selection of alternative fuels. Improved energy efficiency is also an environmental demands, because it can reduce air pollution, acid rain control the incidence and protect the earth from global warming, which may occur due to buildup of carbon dioxide in the atmosphere. One of the alternative fuel is CNG. In motor vehicles, CNG usage advantages include lower price, the exhaust gas is cleaner burning results and the potential source is still very large. Keywords: energy efficiency, fuel, CNG